Betamethasone was more Effective than N-acetylcysteine for Lung Maturation - Oktaviani, Fatmah (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objective: To compare the effectivity of N-acetylcysteine with Betamethasone in fetal lung maturation. Methods: This research was a double blind randomized clinical trials in women threatened by preterm delivery (28 to 34 weeks of gestation). Results: There were 90 subjects randomly assigned to N-acetylcysteine group (n=30), betamethasone group (n=30), and the control group (who had not been given a tocolytic, n=30). Fetal lung maturation was assessed with the p. The values for lung maturation at random were 5 foams. After being tested with the Tapp, there were significant differences between the 3 groups of this study based on analysis of variance (ANOVA) (p = 0.001). The average foam on the N-acetylcysteine was 4.8 ± 1.3 while in the group Betamethasone, was 3.2 ± 1.0, and the average amount of foam in the control group was 5.5 ± 1.6. The end point of the Tapp were mature and immature, which in the N-acetylcysteine group there were 21 subjects (70.0%) with mature lung, Betamethasone groups 28 subjects (93.3%) with mature lungs, whereas in the control group, there were 15 subjects (50.0%) with mature lung. Conclusion: Betamethasone was more effective than N-acetylcysteine for lung maturation in women threatened with preterm delivery. [Indones J Obstet Gynecol 2013; 37-1: 21-5] Keywords: betamethasone, fetal lung maturation, N-acetylcysteine